ZIP9 mediates the effects of DHT on learning, memory and hippocampal synaptic plasticity of male Tfm and APP/PS1 mice - Song, Leigang; Chen, Huan; Qiao, Dan; Zhang, Bohan; Guo, Fangzhen; Zhang, Yizhou; Wang, Chang; Li, Sha; Cui, Huixian (Frontiers in Endocrinology, 2023)
Androgens are closely associated with functions of hippocampal learning, memory, and synaptic plasticity. The zinc transporter ZIP9 (SLC39A9), which is an androgen binding site that is distinct from the androgen receptor (AR), regulates their effects. However, it is still unclear whether androgens regulate their functions in hippocampus of mice through ZIP9. Compared with wild-type (WT) male mice, we found that AR-deficient male testicular feminization mutation (Tfm) mice with low androgen levels had learning and memory impairment, decreased expression of hippocampal synaptic proteins PSD95, drebrin, SYP, and dendritic spine density. Dihydrotestosterone (DHT) supplementation significantly improved these conditions in Tfm male mice, although the beneficial effects disappeared after hippocampal ZIP9 knockdown. To explore the underlying mechanism, we first detected the phosphorylation of ERK1/2 and eIF4E in the hippocampus and found that it was lower in Tfm male mice than in WT male mice, it upregulated with DHT supplementation, and it downregulated after hippocampal ZIP9 knockdown. Next, we found that the expression of PSD95, p-ERK1/2, and p-eIF4E increased in DHT-treated mouse hippocampal neuron HT22 cells, and ZIP9 knockdown or overexpression inhibited or further enhanced these effects. Using the ERK1/2 specific inhibitor SCH772984 and eIF4E specific inhibitor eFT508, we found that DHT activated ERK1/2 through ZIP9, resulting in eIF4E phosphorylation, thus promoting PSD95 protein expression in HT22 cells. Finally, we found that ZIP9 mediated the effects of DHT on the expression of synaptic proteins PSD95, drebrin, SYP, and dendritic spine density in the hippocampus of APP/PS1 mice through the ERK1/2-eIF4E pathway and affected learning and memory. This study demonstrated that androgen affected learning and memory in mice through ZIP9, providing new experimental evidence for improvement in learning and memory in Alzheimer’s Disease with androgen supplementation.